2015
DOI: 10.1111/his.12731
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of chromosomal translocations in small‐bowel diffuse large B‐cell lymphoma

Abstract: Translocations involving IGH are frequent in cases of small-bowel DLBCL. These translocations may be predictive of a favourable clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Multivariate analysis of nodal and extranodal DLBCL revealed that patients with small intestinal involvement had worse OS in the rituximab era . Previous studies have shown that surgery combined with chemotherapy and gene translocation involving the immunoglobulin heavy chain is associated with improved outcome in primary intestinal DLBCL, whereas perforation and age ≥65 years are associated with worse prognosis . However, the biological properties or clinicopathological heterogeneity of primary iDLBCL has not been addressed well in the past because of the paucity of well‐documented cases.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis of nodal and extranodal DLBCL revealed that patients with small intestinal involvement had worse OS in the rituximab era . Previous studies have shown that surgery combined with chemotherapy and gene translocation involving the immunoglobulin heavy chain is associated with improved outcome in primary intestinal DLBCL, whereas perforation and age ≥65 years are associated with worse prognosis . However, the biological properties or clinicopathological heterogeneity of primary iDLBCL has not been addressed well in the past because of the paucity of well‐documented cases.…”
Section: Discussionmentioning
confidence: 99%
“…The macroscopic growth pattern was classified as polypoid, ulcerative, lymphomatous polyposis, diffuse-infiltrating, or mixed by three experienced endoscopists (S.N., T.T., and Y.H.) based on the endoscopic findings in 8 cases and on the surgical excision specimens in 17 cases [6,20,21]. The initial treatment modalities included surgical resection, chemotherapy with a cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP)-based regimen with or without rituximab, radiotherapy, or a combination of them.…”
Section: Subjectsmentioning
confidence: 99%
“…For immunohistochemistry (IHC), we used the primary mouse monoclonal antibodies against CD10 (clone 56C6, 1:100 dilution; Leica Biosystems, Newcastle upon Tyne, UK), bcl-2 (clone 124, 1:100 dilution; Dako), bcl-6 (clone PG-B6p, 1:10 dilution; Dako), MUM1 (clone MUM1p, 1:50 dilution; Dako) and c-myc (clone Y69, 1:100 dilution; Abcam, Cambridge, UK). Samples in which more than 30% of tumor cells were immunoreactive were considered to be positive for CD10, bcl-6 and MUM1 [3,20,21]. Thereafter, tumors were classified as either GCB or non-GCB phenotype according to the algorithm of Hans [25].…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 2 more Smart Citations